Radioactive source film and preparation method and application thereof
Patent Information
- Application Number
- CN202411987604.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-15
AI Technical Summary
The specific activity of materials used in the prior art is too low, resulting in low surface exit activity density and strong self-absorbing effect, which cannot be effectively applied to nuclear batteries and other fields.
A radiosource film including C-14-labeled acetaneniline and modified polyvinyl alcohol film layer is used to improve the specific activity and surface exit activity density by adjusting the material ratio and layer thickness, and reduce the self-absorbing effect.
A radiosource film with higher specific activity, high surface exit activity density and weak self-absorbing effect is achieved, which improves the performance and service life of nuclear batteries.
Smart Images

Figure BDA0005222942450000101 
Figure BDA0005222942450000102 
Figure BDA0005222942450000103
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of battery manufacturing, and in particular to a radioactive source film and a preparation method and application thereof. Background Art
[0002] With the development of modern science and technology, the application of radioisotopes and ionizing radiation is becoming more and more widespread. As an important application of nuclear technology, radioactive sources are making positive contributions to the technological progress of the national economy and the improvement of people's quality of life.
[0003] The ionization, excitation, absorption or scattering effects of the interaction between the ionizing radiation emitted by the radioactive source and the material can obtain valuable information such as the structure, composition, state and non-electrical parameters of the material, which is of great practical significance for the automation of industrial production processes and product quality control. The radioactive source is actually an information source. When matched with a sensitive radiation sensor and an electronic computer that can quickly process a large amount of information, it can form an advanced information system that is widely used in analysis, detection, alarm, flaw detection and other fields. At present, this information system has further enriched the world's high-tech market in the form of products such as isotope instruments and nuclear analysis devices. The radioactive source also has the function of material modification and medical treatment of diseases. The ionizing radiation emitted by the radioactive source can produce profound physical, chemical and biological effects on the material, making the radioactive source an efficient material processing method and disease treatment tool. In fact, the radioactive source has played a significant role in the radiation processing of polymer materials, radiation disinfection of medical supplies and radiation preservation of food. Radiotherapy has now become one of the three traditional methods of cancer treatment, and is equally important as surgical treatment and chemotherapy. In addition, the radioactive source is also a unique energy source. The decay energy of radioactive nuclides can be converted into heat energy, thus making radioisotope heat sources. The decay energy of nuclides can also be further converted into electrical energy (nuclear batteries), which are used as an irreplaceable power source in spacecraft, ocean development, polar exploration, etc. In short, the technical advantages of radioactive sources have expanded their application scope.
[0004] The C-14 radiovoltaic isotope battery is a small radiation device that uses C-14 radioactive isotopes to generate electricity. The device is mainly composed of a C-14 radioactive source film, a semiconductor energy conversion device, and a packaging shell. Therefore, it is crucial to prepare a thin film beta radiation source with high surface activity, high specific activity, and high stability.
[0005] In the prior art, the specific activity of the material used in the radioactive source is too low, which makes it sufficient as a standard source and signal detection source, but far from enough as an energy supply source such as a nuclear battery. The surface emission activity density of the radioactive source is in the order of μCi, and the generated electrical signal is very weak and cannot be used. In order to solve the above problem, barium carbonate is used as the radioactive source material in the prior art, but in order to avoid the release and contamination of the radioactive source, the radioactive source needs to be placed between the organic film and the aluminum-plated film to reduce the surface emission activity density.
[0006] Therefore, there is an urgent need to develop a coating method and material that has high specific activity and can directly and completely solidify the C-14 radiation source. Summary of the invention
[0007] In view of the above-mentioned shortcomings of the prior art, the purpose of the present invention is to provide a radioactive source film and its preparation method and use. The radioactive source film described in the present application solves the problems of the radioactive source material used in the prior art having too low specific activity, low surface emission activity and strong self-absorption effect.
[0008] To achieve the above objectives and other related objectives, the present invention is achieved through the following technical solutions.
[0009] The first aspect of the present invention discloses a radioactive source film, which comprises a radioactive source layer and a modified polyvinyl alcohol film layer; the raw materials of the radioactive source layer comprise C-14 labeled acetanilide and an organic solvent, and the mass ratio of the organic solvent to the C-14 labeled acetanilide is (0.1-1):1; the raw materials of the modified polyvinyl alcohol film layer comprise polyvinyl alcohol, a modifier and a solvent; the modifier is selected from one or more of boric acid and montmorillonite; based on the mass of the solvent, the amount of the polyvinyl alcohol is 4-10wt%; based on the mass of the polyvinyl alcohol, the amount of the modifier is 0.1-10wt%.
[0010] Preferably, the thickness of the radiation source layer is 5-200 μm.
[0011] Preferably, based on the volume of the radiation source layer, the amount of C-14 labeled acetanilide is 0.045-0.135 mg / (cm×cm×μm), wherein cm×cm×μm corresponds to the length, width and thickness of the radiation source layer in sequence, and the volume is the product of the three.
[0012] For example, the content of C-14 labeled acetanilide can be 0.045-0.09 mg / (cm×cm×μm), 0.09-0.1 mg / (cm×cm×μm), 0.1-0.11 mg / (cm×cm×μm), 0.11-0.12 mg / (cm×cm×μm), and 0.12-0.135 mg / (cm×cm×μm).
[0013] Preferably, the mass ratio of the organic solvent to the C-14 labeled acetanilide is (0.25-1): 1. For example, the mass ratio of the organic solvent to the C-14 labeled acetanilide can be (0.25-0.4): 1, (0.4-0.5): 1, (0.5-0.6): 1, (0.6-0.75): 1, (0.75-0.9): 1, (0.9-1): 1.
[0014] In a specific embodiment, the mass of the organic solvent is sufficient as long as it can dissolve the C-14 labeled acetanilide. If the mass of the organic solvent is too much, when the organic solvent evaporates during subsequent film formation, the C-14 radioactive source will escape into the air with the organic solvent, affecting the safety of the experiment; if the mass of the organic solvent is too little, the C-14 labeled acetanilide cannot be completely dissolved, affecting the uniformity of the distribution of the radioactive source in the radioactive source layer.
[0015] Preferably, based on the mass of the solvent, the amount of polyvinyl alcohol is 5.5-8.5 wt%, such as 5.5-6 wt%, 6-6.5 wt%, 6.5-7 wt%, 7-7.5 wt%, 7.5-8 wt%, 8-8.5 wt%.
[0016] In a specific embodiment, the amount of polyvinyl alcohol used only needs to meet the requirements of subsequent drying and film formation. If the content of polyvinyl alcohol is too high, the viscosity is too high to be coated, and excessive shrinkage occurs during drying and film formation, which is not conducive to the shaping of the radiation source film.
[0017] Preferably, based on the mass of the polyvinyl alcohol, the amount of the modifier is 1-10wt%, such as 1-2wt%, 2-3wt%, 3-4wt%, 4-5wt%, 5-6wt%, 6-7wt%, 7-8wt%, 8-9wt%, 9-10wt%.
[0018] In actual application scenarios, different thicknesses of radiation source layers can be prepared according to the needs of different surface emission powers. If a product with a higher single-chip surface emission power is required, a thicker radiation source layer, such as a 120-200μm layer, can be prepared; if costs need to be reduced, a thinner radiation source layer, such as a 10-120μm layer, can be prepared.
[0019] More preferably, the thickness of the radiation source layer is 10-50 μm. For example, the thickness of the radiation source layer can be 10-20 μm, 20-30 μm, 30-40 μm, 40-50 μm. When the thickness of the radiation source layer is 10-50 μm, the source efficiency and surface emission power of the radiation source film are both high.
[0020] Preferably, the thickness of the modified polyvinyl alcohol film layer is 0.1-3 μm. For example, the thickness of the modified polyvinyl alcohol film layer may be 0.1-0.5 μm, 0.5-1 μm, 1-1.5 μm, 1.5-2 μm, 2-2.5 μm, or 2.5-3 μm.
[0021] Preferably, the modifier is boric acid and montmorillonite. When the modifier is dispersed in the polyvinyl alcohol matrix, it can form a strong interaction with the polyvinyl alcohol molecules, thereby improving the mechanical strength and toughness of the film; improving thermal stability and inhibiting thermal degradation of polyvinyl alcohol, thereby increasing the use temperature range of the radiation source film; the modified radiation source film has better environmental adaptability, such as UV resistance and aging resistance.
[0022] More preferably, the mass ratio of the boric acid to the montmorillonite is 1:(0.1-1). Further, the mass ratio of the boric acid to the montmorillonite is 1:(0.2-1). For example, the mass ratio of the boric acid to the montmorillonite is 1:(0.2-0.4), 1:(0.4-0.6), 1:(0.6-0.8), 1:(0.8-1).
[0023] The layered structure of the montmorillonite interacts strongly with the polyvinyl alcohol molecules, forming a maze-like path in the material, effectively preventing the penetration of gas and liquid molecules, while enhancing the tensile strength and tear resistance of the film, making the film more reliable when subjected to physical impact and mechanical stress.
[0024] Preferably, the number average molecular weight of the polyvinyl alcohol is 20,000 to 200,000. For example, the number average molecular weight of the polyvinyl alcohol may be 20,000 to 30,000, 30,000 to 50,000, 50,000 to 100,000, or 100,000 to 200,000. Considering the influence of the density of polyvinyl alcohol on the strength of the self-absorption effect of the final radiation source film and the proportion of bremsstrahlung radiation, it is most preferred that the number average molecular weight of the polyvinyl alcohol is 20,000 to 50,000.
[0025] Preferably, the density of the polyvinyl alcohol is 1.2 to 1.31 g / cm 3 The density of the polyvinyl alcohol can be 1.2 to 1.22 g / cm 3 1.22~1.25g / cm3 1.25~1.31g / cm 3 The C-14 radioactive source is pure β decay with an average energy of 49.47keV. Therefore, the higher the density of the material matrix and the larger the atomic number, the more severe the self-absorption effect and the higher the bremsstrahlung ratio. The density of the polyvinyl alcohol is lower than that of other radioactive source materials (such as polyethylene terephthalate), and the blocking effect of the radiation is weaker. The weaker self-absorption effect enables β rays to pass through the radioactive source film with higher energy and less energy loss, thus maintaining its penetrating power.
[0026] Preferably, the montmorillonite is selected from one or more of sodium-based montmorillonite, calcium-based montmorillonite and magnesium-based montmorillonite.
[0027] More preferably, the montmorillonite is sodium montmorillonite. Compared with calcium montmorillonite and magnesium montmorillonite, the sodium montmorillonite has better swelling and cation exchange properties, better dispersibility in water media, and higher thermal stability.
[0028] More preferably, the ion exchange capacity of the sodium-based nano-montmorillonite is 80 to 150 mmol / 100 g. Further, the ion exchange capacity of the sodium-based nano-montmorillonite is 120 to 145 mmol / 100 g.
[0029] More preferably, the aspect ratio of the sodium-based nano-montmorillonite is 200-400.
[0030] More preferably, the specific gravity of the sodium-based nano-montmorillonite is 2.3 to 3 g / cm 3 The specific gravity of the sodium-based nano-montmorillonite may be 2.3 to 2.6 g / cm 3 , 2.6~3g / cm 3 .
[0031] More preferably, the water content of the sodium-based nano-montmorillonite is 8-15wt%. For example, the water content of the sodium-based nano-montmorillonite may be 8-12wt%, 12-15wt%.
[0032] More preferably, the pH value of the sodium-based nano-montmorillonite is 9.5-10.5.
[0033] More preferably, the average particle size of the sodium-based nano-montmorillonite is 16 to 22 nm.
[0034] Preferably, the particle size of the montmorillonite is 10-100 nm. For example, the particle size of the montmorillonite may be 10-16 nm, 16-22 nm, 22-36 nm, 36-46 nm, 46-56 nm, 56-66 nm, 66-76 nm, 76-86 nm, 86-96 nm, 96-100 nm.
[0035] Preferably, the solvent is water.
[0036] Preferably, the raw material of the modified polyvinyl alcohol film layer further comprises glycerol, and the amount of the glycerol is 0.01-0.5wt% based on the mass of the solvent, such as 0.01-0.1wt%, 0.1-0.2wt%, 0.2-0.3wt%, 0.3-0.4wt%, 0.4-0.5wt%.
[0037] It should be noted that the effect of the amount of the modifier on the source activity and the surface emission activity density of the radiation source film can be ignored.
[0038] Preferably, the number of C-14 labels in each C-14 labeled acetanilide molecule is 1 to 8. For example, the number of C-14 labels can be 1, 2, 3, 4, 5, 6, 7, or 8.
[0039] The labeling amount of the C-14 labeled acetanilide and the preparation method thereof can be arbitrarily selected according to experimental conditions.
[0040] Preferably, the preparation method of the C-14 labeled acetanilide comprises one or more of organic chemical synthesis, radionuclide labeling technology, and rapid synthesis method.
[0041] Preferably, the organic solvent is selected from one or more of methanol, ethanol, propanol and acetone.
[0042] The applicant found that the dispersion uniformity of non-C-14 labeled acetanilide in different organic solvents is different. In the above organic solvents, the solubility of C-14 labeled acetanilide is good and the dispersion is uniform. The above organic solvents have a low evaporation temperature, which is conducive to the subsequent formation of a radiation source layer. In addition, the radiation source layer formed using the above organic solvents as raw materials is dense and smooth, and the radioactive material is evenly dispersed.
[0043] The second aspect of the present invention discloses a method for preparing the above-mentioned radiation source film. The preparation method comprises the following steps: mixing the raw materials of the radiation source layer, coating it on a substrate, heating to evaporate an organic solvent to form the radiation source layer; mixing the raw materials of the modified polyvinyl alcohol film layer, coating it on the radiation source layer and curing it.
[0044] Preferably, the mixing temperature of the raw materials of the modified polyvinyl alcohol film layer is 80-100° C. For example, the mixing temperature of the raw materials of the modified polyvinyl alcohol film layer may be 80-85° C., 85-90° C., 90-95° C., or 95-100° C.
[0045] Preferably, the mixing time of the raw materials of the modified polyvinyl alcohol film layer is 0.5 to 3 hours. For example, the mixing time of the raw materials of the modified polyvinyl alcohol film layer can be 0.5 to 1 hour, 1 to 1.5 hours, 1.5 to 2 hours, 2 to 2.5 hours, or 2.5 to 3 hours.
[0046] More preferably, the raw materials of the modified polyvinyl alcohol film layer are mixed and coated on the radiation source layer to a coating thickness of 2 to 5 μm.
[0047] More preferably, the curing is performed by heating.
[0048] Furthermore, the temperature of the heating and curing is 35-65°C. For example, the temperature of the heating and curing can be 35-40°C, 40-45°C, 45-50°C, 50-55°C, 55-60°C, or 60-65°C.
[0049] Furthermore, the heating and curing time is 3 to 10 minutes. For example, the heating and curing time can be 3 to 5 minutes, 5 to 7 minutes, 7 to 9 minutes, or 9 to 10 minutes.
[0050] If the heating and curing time is too long or the temperature is too high, the modified polyvinyl alcohol film layer becomes brittle, the mechanical properties are reduced, and it is impossible to adhere well to the radiation source layer.
[0051] More preferably, the temperature of heating to evaporate the organic solvent is 35-65° C. For example, the temperature of heating to evaporate the organic solvent may be 35-40° C., 40-45° C., 45-50° C., 50-55° C., 55-60° C., 60-65° C.
[0052] More preferably, the heating time for evaporating the organic solvent is 5 to 20 minutes. For example, the heating time for evaporating the organic solvent can be 5 to 7 minutes, 7 to 9 minutes, 9 to 12 minutes, 12 to 15 minutes, 15 to 17 minutes, or 17 to 20 minutes.
[0053] More preferably, after further coating the modified polyvinyl alcohol mother solution and heating and drying, the step further comprises cutting off the modified polyvinyl alcohol film layer that does not overlap with the radiation source layer.
[0054] Taking into account the cost and danger of radioactive materials, preferably, the preparation method comprises the following steps: preparing a hollow mold and placing it on a substrate, first coating the mixed liquid formed by mixing the raw materials for the modified polyvinyl alcohol layer around the outer periphery of the mold and heating and curing it; then coating the mixed liquid formed by mixing the raw materials for the radiation source layer on the hollow part of the mold and heating to evaporate the organic solvent to form a radiation source layer; finally, removing the mold and further coating the mixed liquid formed by mixing the raw materials for the modified polyvinyl alcohol layer on the radiation source layer and heating and curing it.
[0055] The third aspect of the present invention also discloses the use of the radioactive source film as a standard source and / or a signal detection source and / or a nuclear battery power generation energy source.
[0056] Compared with the prior art, the present invention has the following beneficial effects:
[0057] 1. The raw material of the radiation source film claimed in the present invention includes polyvinyl alcohol, so that the radiation source film has the characteristics of good film-forming property, no irritating odor, stable chemical properties, good flexibility, strong thermoplasticity, good adhesion, strong surface light transmittance, etc.
[0058] 2. The radioactive source film claimed in the present invention has a low density, does not contain metal elements with high atomic numbers, has a weaker blocking effect on radiation, and has a weaker self-absorption effect, thereby ensuring that the performance of the nuclear battery is not affected to the greatest extent, thereby improving the processing performance and use performance of the film in the nuclear battery.
[0059] 3. Compared with the radiation source film in the prior art, the radiation source film described in the present application has a larger saturated self-absorption thickness. Therefore, the allowable error in the film-forming process of the radiation source film described in the present application is larger, and the upper and lower deviations of several microns or even more than ten microns have little effect on the performance of the radiation source film.
[0060] 4. The raw materials of the radioactive source film of the present invention include C-14 labeled acetanilide, which has a large specific activity. The specific activities of unit mass of polymethyl methacrylate and barium carbonate are 7.7×10 10 Bq / g and 1.16×10 10 Bq / g, while the specific activity of acetanilide is 1.22×10 11 Bq / g, if all 8 carbon atoms of acetanilide are labeled with C-14, each carbon atom can independently contribute to the specific activity of C-14, and its specific activity will be 8 times that of barium carbonate or polymethyl methacrylate.
[0061] 5. The radioactive source film of the present invention has enhanced mechanical strength by modifying polyvinyl alcohol. The stability of the modified polyvinyl alcohol film layer enables it to withstand β-ray radiation without chemical or physical changes, thereby maintaining the permeability of the film, providing a more reliable material selection for radiovoltaic effect nuclear battery coating technology, minimizing the risk of radioactive source leakage during the nuclear battery manufacturing process, and improving the mechanical properties and durability of the radioactive source film in the nuclear battery, thereby extending the service life of the C-14 nuclear battery.
[0062] 6. The preparation method of the radioactive source film of the present invention can ensure the film size and shape of the radioactive source film, avoiding waste caused by cutting scraps. At the same time, the radioactive source film can be made into films of different thicknesses and shapes through simple processing technology, which provides flexibility for designing nuclear battery applications with specific transmittance requirements, making it more cost-effective in long-term use, and the environmentally friendly raw material selection further improves the sustainability of the material. BRIEF DESCRIPTION OF THE DRAWINGS
[0063] Figure 1 Shown is a schematic diagram of the structure of the radiation source film described in this application in a battery.
[0064] Figure 2 Shown is a schematic diagram of the radioactive source sheet adsorption process in Comparative Example 1.
[0065] Figure 3 Shown is a schematic diagram of the sealing and casing of the radioactive source piece in Comparative Example 1.
[0066] Component number description
[0067] 1 Packaging unit
[0068] 11. First transducer
[0069] 12. First upper electrode
[0070] 121 grid electrode
[0071] 122 Surround electrode
[0072] 13. First back electrode
[0073] 21 Second transducer
[0074] 22. Second upper electrode
[0075] 221 grid electrode
[0076] 222 Surround Electrode
[0077] 23. Second back electrode
[0078] 31. Radioactive source film
[0079] 41 Metal bonding layer
[0080] 411 Ring metal part
[0081] 412 Lead out metal part
[0082] 51 Back metal layer DETAILED DESCRIPTION
[0083] The following is a description of the implementation of the present invention by means of specific embodiments. Those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification.
[0084] Before further describing the specific embodiments of the present invention, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below; it should also be understood that the terms used in the examples of the present invention are intended to describe specific embodiments, rather than to limit the scope of protection of the present invention. The test methods in the following examples without specifying specific conditions are generally carried out under conventional conditions or under conditions recommended by the manufacturers.
[0085] When the embodiments give numerical ranges, it should be understood that, unless otherwise specified in the present invention, both endpoints of each numerical range and any numerical value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those generally understood by those skilled in the art. In addition to the specific methods, equipment, and materials used in the embodiments, according to the grasp of the prior art by those skilled in the art and the record of the present invention, any methods, equipment, and materials of the prior art similar or equivalent to the methods, equipment, and materials described in the embodiments of the present invention can also be used to realize the present invention.
[0086] In this application, in view of the technical problems in the prior art that the material used in the radioactive source has low specific activity, low surface emission activity density, and strong self-absorption effect, the applicant provides a radioactive source film and its preparation method and use. The radioactive source film described in this application has a higher specific activity of the material used, high surface emission activity density, weak self-absorption effect, small proportion of bremsstrahlung radiation, and high radioactive source efficiency.
[0087] Specific activity refers to the radioactivity produced by a unit amount of radioactive material.
[0088] Bremsstrahlung means that when β-rays enter the material, they will have elastic and inelastic collisions with the electrons in the atomic shell of the material, and will have elastic and inelastic collisions with the atomic nuclei of the material. The energy loss caused by the inelastic collision between β-rays and the electrons in the atomic shell of the material is called ionization loss. The energy loss caused by the inelastic collision between β-rays and the atomic nuclei of the material is called radiation loss. This process also radiates X-rays outward. The X-rays generated by this process are called bremsstrahlung.
[0089] The self-absorption effect refers to the following: β-radiation sources and α-radiation sources emit charged particles, and these particles will be lost in the process of passing through the radiation source material itself and emitting to the outside, because the radiation source has thickness. Therefore, the surface emission power of the radiation source will not increase with the increase of the amount of radiation source used, but when the radiation source reaches a certain thickness, the surface emission power density of the radiation source will reach a saturation value. If the thickness of the radiation source is further increased, the surface emission power of the radiation source will not continue to increase, but the cost will increase dramatically. Therefore, the thicker the β-radiation source film is, the better.
[0090] The efficiency of a radiation source refers to the ratio of the number of particles emitted from the surface of the radiation source per second to the total number of particles emitted per second.
[0091] The preparation method of C-14 labeled acetanilide in the present application is an organic chemical synthesis method, specifically, C-14 labeled barium carbonate is weighed according to the target C-14 amount, and C-14 labeled barium carbonate is used to react with sulfuric acid to generate C-14 labeled carbon dioxide; C-14 labeled carbon dioxide reacts with lithium to generate C-14 labeled lithium carbide; C-14 labeled lithium carbide reacts with water to generate C-14 labeled acetylene; C-14 labeled acetylene is converted into C-14 labeled benzene under the influence of an acetylene trimerization catalyst, so that each carbon on the C-14 labeled benzene is labeled; and C-14 labeled acetanilide is further generated through an organic synthesis reaction.
[0092] In the following specific examples, the C-14-labeled barium carbonate was weighed based on the fact that each C-14-labeled acetanilide molecule contained 6 C-14 atoms.
[0093] The technical scheme and technical effects of the present invention are further described and explained through the following specific embodiments and implementation effects.
[0094] In the preferred embodiment of the present application, the number average molecular weight of polyvinyl alcohol is 30,000 to 500,000; and the montmorillonite is sodium-based nano-montmorillonite.
[0095] In the following specific examples, the ion exchange capacity of the sodium-based nano-montmorillonite is 145 mmol / 100 g, the aspect ratio is 300, and the specific gravity is 2.6 g / cm 3 , moisture content is 12wt%, pH value is 10, and average particle size is 18nm.
[0096] The substrate in the present application is selected to have a smooth and flat surface to facilitate film formation, and preferably an easily peelable surface to facilitate substrate removal, such as glass, alumina ceramics, aluminum, and silica gel. In the following specific embodiments of the present application, an aluminum substrate is used.
[0097] In the following embodiments of the present application, a specific method for forming a radioactive source thin film is adopted in consideration of saving the cost and danger of radioactive source materials, controlling the shape and thickness of the radioactive source layer, and facilitating subsequent testing, including the following steps: placing a through hollow mold on a substrate, coating a raw material mixture of the radioactive source layer in the hollow mold and heating to evaporate an organic solvent to form the radioactive source layer; removing the mold, coating the raw material mixture of the modified polyvinyl alcohol film layer on the radioactive source layer and curing it.
[0098] In one embodiment, the hollow mold is a rectangular parallelepiped with a through hole. In the following embodiment, the length*width*height of the outer contour of the rectangular parallelepiped is 3cm*3cm*2mm; the through hole is a rectangular parallelepiped and the length*width of the through hole is 1cm*1cm, where the difference of 2cm is the size of the mold itself (e.g., the width and length are both 2cm).
[0099] Further considering the physical and mechanical properties of the mixed liquid of the radioactive source layer raw materials of the present application, in order to prevent the mixed liquid of the radioactive source layer raw materials from entering the gap between the mold and the substrate and causing waste. In a more specific embodiment, the preparation method of the radioactive source film further includes the following steps: placing the hollow mold on the substrate, first coating the mixed liquid of the modified polyvinyl alcohol layer raw materials around the mold and heating to cure; then coating the mixed liquid of the radioactive source layer raw materials in the hollow part of the mold and heating to evaporate the organic solvent; finally removing the mold, further coating the mixed liquid of the modified polyvinyl alcohol layer raw materials and heating to cure.
[0100] The mixed liquid of the modified polyvinyl alcohol layer raw materials is first coated around the mold and heated to solidify, so that the mixed liquid of the modified polyvinyl alcohol layer raw materials solidifies into a film around the mold, forming a barrier frame in the hollow area, preventing the mixed liquid of the radiation source layer raw materials from entering the gap between the mold and the substrate and causing waste.
[0101] In practical application scenarios, the material of the mold can be arbitrarily selected according to experimental needs, such as one or more of aluminum, silicone, glass, and ceramic. In the following specific embodiments of the present application, the material of the mold is aluminum.
[0102] The present application also discloses the use of the radioactive source film as a power source for a nuclear battery. In a specific embodiment, the position of the radioactive source film in the nuclear battery is as follows: Figure 1 shown.
[0103] In a Figure 1In the specific nuclear battery shown, the packaging structure of the nuclear battery includes a packaging unit 1, which includes: a first transducer 11 and a second transducer 21, which respectively include opposite first and second surfaces, the first surface of the first transducer 11 is provided with a first upper electrode 12, and the second surface is provided with a first back electrode 13, the first surface of the second transducer 21 is provided with a second upper electrode 22, and the second surface is provided with a second back electrode 23, the first upper electrode 12 and the second upper electrode 22 include grid electrodes 121, 221 and surrounding electrodes 122, 222 surrounding the grid electrodes 121, 221 and connected to the grid electrodes 121, 221; a radiation source film 31, the radiation source film 31 is provided between the grid electrode 121 of the first upper electrode 12 and the grid electrode 221 of the second upper electrode 22; a metal bonding layer 41, including an annular metal layer bonded between the surrounding electrodes of the first upper electrode 12 and the second upper electrode 22, and a lead-out metal portion 412 connected to one side of the annular metal portion 411 and extending outside the surrounding metal portion. The first transducer 11 and the second transducer 21 further include a back metal layer 51 , which covers the surface of the first back electrode 13 and the second back electrode 23 and extends from the other side opposite to the lead-out metal portion 412 to outside the first back electrode 13 and the second back electrode 23 .
[0104] In an actual power generation scenario, the radiation source film 31 is disposed between the grid electrode 121 of the first upper electrode 12 and the grid electrode 221 of the second upper electrode 22 , and the radiation source film emits electrons to the outside to generate electricity.
[0105] In the following embodiments of the present application: the radiation source surface emission activity density, the radiation source surface emission power density, the source efficiency and the source activity are obtained by simulation calculation using the Monte Carlo simulation tool GEANT4. Specifically:
[0106] The emission activity density on the surface of the radiation source:
[0107]
[0108] Where A_Surface is the surface emission activity density, P1~P6 are the emission probabilities of the six surfaces of the rectangular radiation source, A_Total is the total activity, and S is the surface area of the radiation source.
[0109] The power density of the radiation source surface:
[0110]
[0111] Where W Surface is the surface emission power density, E1~E6 is the energy deposited on the six surfaces of the rectangular radiation source, A Total is the total activity, and S is the surface area of the radioactive source.
[0112] Source efficiency =
[0113]
[0114] Among them, W Surface is the surface output power density, S is the surface area of the radiation source, W Total is the total power.
[0115] Source activity:
[0116]
[0117] Among them A Total is the total activity, S Bottom is the bottom area, H is the height, ρ is the material density, M is the relative atomic mass of the material, N A is Avogadro's constant, T 1 / 2 The half-life of the radioactive source
[0118] The source activity can also be obtained by a detection method using liquid scintillator detection.
[0119] Example 1
[0120] This embodiment provides a specific radiation source film and a method for preparing the same.
[0121] Among them, the raw materials of the modified polyvinyl alcohol film layer and the mixing method thereof include the following:
[0122] Weigh 0.85g of boric acid and 0.51g of sodium-based nano-montmorillonite and dissolve them in 200mL of distilled water, and stir continuously until mixed evenly to obtain a mixed solution; then weigh 17g of polyvinyl alcohol, the number average molecular weight of the polyvinyl alcohol is 40,000, and add it to the mixed solution. Under the condition of heating in a water bath at 95°C, stir continuously for 1.5h using ultrasonic oscillation to completely dissolve and disperse the boric acid, sodium-based nano-montmorillonite and polyvinyl alcohol, and mix evenly to obtain a modified polyvinyl alcohol solution; finally, add 1g of glycerol to the modified polyvinyl alcohol solution, continue stirring for 1 hour, then cool to room temperature, put it in a vacuum drying oven to degas to room temperature, and put it in a vacuum drying oven to degas until there are no bubbles for use.
[0123] The raw materials of the radiation source layer and the mixing method thereof include the following:
[0124] 1.35 mg of C-14 labeled acetanilide and 1.35 mg of methanol (mass ratio 1:1) were mixed to obtain a radioactive source mother solution. Ultrasonic vibration was used during mixing to ensure uniform mixing.
[0125] The film forming method of the radioactive source thin film comprises the following steps:
[0126] The hollow mold is placed on a glass plate of a heating platform, and a modified polyvinyl alcohol solution is coated around the mold to form a barrier frame of the hollow area, and the mold is heated at 50° C. for 6 minutes to be cured;
[0127] Add the radioactive source mother liquid dropwise into the hollow hole, and heat it on a heating plate at 50°C for 10 minutes to dry and evaporate the organic solvent in the radioactive source mother liquid;
[0128] The hollow mold was removed, and the modified polyvinyl alcohol solution was further coated. The scraper height of the coating machine was set to be 3 μm higher than the opening on the heating plate, the temperature of the heating table was set to 60° C., the modified polyvinyl alcohol solution on the surface was scraped flat at a uniform speed, and the preparation of the radiation source film was completed after heating for 10 minutes.
[0129] The test results show that:
[0130] (1) The thickness of the radiation source layer in the radiation source film of this embodiment is 10 μm;
[0131] (2) Source activity is 2.980 mCi;
[0132] (3) The radiation source surface emission activity density is 1.266 Ci / cm 2 ;
[0133] (4) The power density of the radiation source surface is 0.445 μW / cm 2 ;
[0134] (5) The source efficiency is 82%.
[0135] Example 2
[0136] The difference between this embodiment and embodiment 1 is that 2.7 mg of C-14 labeled acetanilide is weighed; methanol is weighed in a ratio of C-14 labeled acetanilide to organic solvent of 1:0.75;
[0137] The test results show that:
[0138] 1) The thickness of the radiation source layer in the radiation source film of this embodiment is 20 μm;
[0139] 2) The source activity is 5.961 mCi;
[0140] 3) The radiation source surface emission activity density is 2.146Ci / cm 2 ;
[0141] 4) The power density of the radiation source surface is 0.752μW / cm 2 ;
[0142] 5) The source efficiency is 70%.
[0143] Example 3
[0144] The difference between this embodiment and embodiment 1 is that 5.4 mg of C-14 labeled acetanilide and 5.4 mg of methanol are weighed; 11 g of polyvinyl alcohol, 0.55 g of boric acid, and 0.33 g of sodium-based nano-montmorillonite are weighed;
[0145] The test results show that:
[0146] 1) The thickness of the radiation source layer in the radiation source film of this embodiment is 40 μm;
[0147] 2) The source activity is 11.922 mCi;
[0148] 3) The radiation source surface emission activity density is 3.212Ci / cm 2 ;
[0149] 4) The power density of the radiation source surface is 1.122μW / cm 2 ;
[0150] 5) The source efficiency is 52%.
[0151] Example 4
[0152] The difference between this example and Example 1 is that 16.2 mg of C-14 labeled acetanilide and 16.2 mg of methanol are weighed;
[0153] The test results show that:
[0154] 1) The thickness of the radiation source layer in the radiation source film of this embodiment is 120 μm;
[0155] 2) The source activity is 35.765 mCi;
[0156] 3) The radiation source surface emission activity density is 4.257Ci / cm 2 ;
[0157] 4) The power density of the radiation source surface is 1.470μW / cm 2 ;
[0158] 5) The source efficiency is 23%.
[0159] Comparative Example 1
[0160] This comparative example provides a standard C-14 radiation source film based on polymethyl methacrylate and a preparation method thereof.
[0161] The preparation method of the radioactive source film in this comparative example is: C-14 replaces one or more C-12 in the monomers before polymerization of polymethyl methacrylate with C-14 through the nuclide labeling technology to make it radioactive. The specific scheme is to first prepare C-14 labeled methacrylic acid monomers, then polymerize them into methyl methacrylate, and apply them on an aluminum substrate to make a thin organic film source.
[0162] The starting monomers are measured by a liquid scintillation counter to obtain the activity value per gram of polymer, and the surface particle emission rate of the organic film source is measured by an end window counter tube.
[0163] The test results show that:
[0164] For a 1 mm thick film, the source activity is 1.85×10 6 Bq / cm 2 , the emission activity density on the surface of the radiation source is 1.3×10 6 cm -2 min -1 .
[0165] It can be seen that the surface emission activity density of the thin film radioactive source in the comparative example is of the μCi order, and the generated electrical signal is very weak and cannot be used. The surface emission activity density of the radioactive source film in the present application is higher. At the same time, since the C-14 labeled acetanilide in the present application has a higher specific activity and the density of polyvinyl alcohol is low, it can be analyzed that the radioactive source film in the present application has a weaker self-absorption effect than the film in comparative example 1, a small proportion of bremsstrahlung radiation is generated, and the radioactive source efficiency is high.
[0166] Comparative Example 2
[0167] This comparative example provides a radioactive source film based on C-14 labeled barium carbonate and a preparation method thereof.
[0168] The preparation method of the radioactive source film in this comparative example is: 0.25g of Ba 14 CO 3 Put the raw materials into a glass bottle, add appropriate amount of acetone, then add magnetite and ZrO 2 Grinding ball. Among them, ZrO 2 Grinding balls were used as grinding media and stirred with a magnetic stirrer for 2 h to obtain a uniformly distributed carbonate powder suspension. Figure 1 As shown, a predetermined volume of barium carbonate powder suspension is taken with a 2.5 mL syringe, and the predetermined volume of carbonate powder suspension is injected into a filter device (with an adsorption membrane inside). After the syringe injects all the suspension into the filter device, the filtration adsorption is completed. The filter device is opened, and the adsorption membrane is placed in a fume hood for 3 minutes to obtain a radioactive source sheet.
[0169] like Figure 2As shown, take an organic film and a PET aluminum-coated film, place the radiation source carrier between the organic film and the PET aluminum-coated film, seal with a film sealing machine, and cut to obtain a source sheet. Take a radiation source shell, encapsulate the source sheet in the radiation source shell, and obtain a C-14 radiation source with a high emissivity.
[0170] The test results show that:
[0171] 20 μm thick film, source activity is 5.6×10 6 Bq / cm 2 ; The emission activity density on the surface of the radiation source is 1.1×10 6 Bq / cm 2 , source efficiency 19.64%.
[0172] It can be seen that the emission activity density on the surface of the thin film radiation source in the comparative example is of the μCi order, and the generated electrical signal is very weak and cannot be applied to nuclear battery power generation. The emission activity density on the surface of the radiation source film described in the present application is higher. In addition, at the same thickness, the source efficiency of the radiation source film described in the present application is also higher.
[0173] From the above test results, it can be concluded that, compared with the radioactive source film based on C-14 labeled barium carbonate and the standard C-14 radioactive source film based on polymethyl methacrylate, the material used in the radioactive source film described in the present application has a higher specific activity, a high surface emission activity density, a low self-absorption effect, a small proportion of bremsstrahlung radiation, and a high source efficiency.
[0174] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A radioactive source film, characterized in that: The radiation source film comprises a radiation source layer and a modified polyvinyl alcohol film layer; The raw materials of the radiation source layer include C-14 labeled acetanilide and an organic solvent, and the mass ratio of the organic solvent to the C-14 labeled acetanilide is 0.1 to 1:1; The raw materials of the modified polyvinyl alcohol film layer include polyvinyl alcohol, a modifier and a solvent; the modifier is selected from one or more of boric acid and montmorillonite; based on the mass of the solvent, the amount of the polyvinyl alcohol is 4 to 10 wt%; based on the mass of the polyvinyl alcohol, the amount of the modifier is 0.1 to 10 wt%.
2. The radiation source film according to claim 1, characterized in that: Based on the volume of the radiation source layer, the content of the C-14 labeled acetanilide is 0.045-0.135 mg / (cm×cm×μm); And / or, the thickness of the radiation source layer is 5 to 200 μm, and the thickness of the modified polyvinyl alcohol film layer is 0.01 to 3 μm; And / or, the number average molecular weight of the polyvinyl alcohol is 20000 to 200000; and / or, the solvent is water; And / or, the raw material of the modified polyvinyl alcohol film layer further includes glycerol, and the amount of the glycerol is 0.01-0.5wt% based on the mass of the polyvinyl alcohol.
3. The radiation source film according to claim 1, characterized in that: The montmorillonite is selected from one or more of sodium montmorillonite, calcium montmorillonite and magnesium montmorillonite; And / or, the particle size of the montmorillonite is 10 to 100 nm.
4. The radiation source film according to claim 1, characterized in that: The number of C-14 labels in each of the C-14-labeled acetanilide molecules is 1 to 8; And / or, the organic solvent is selected from one or more of methanol, ethanol, propanol and acetone.
5. A method for preparing a radioactive source film as claimed in any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: mixing the raw materials of the radiation source layer, coating it on a substrate, and heating to evaporate an organic solvent to form the radiation source layer; mixing the raw materials of the modified polyvinyl alcohol film layer, coating it on the radiation source layer, and curing it.
6. The preparation method according to claim 5, characterized in that: The mixing temperature of the raw materials of the modified polyvinyl alcohol film layer is 80-100°C; And / or, the mixing time of the raw materials of the modified polyvinyl alcohol film layer is 0.5 to 3 hours.
7. The preparation method according to claim 5, characterized in that: The temperature of heating to evaporate the organic solvent is 35 to 65° C.; And / or, the heating time for evaporating the organic solvent is 5 to 20 minutes.
8. The preparation method according to claim 5, characterized in that: The curing is performed by heating; the temperature of the heating curing is 35 to 65° C. and the time is 3 to 10 minutes.
9. The preparation method according to claim 5, characterized in that: The preparation method comprises the following steps: placing a hollow mold on a substrate, first coating the outer periphery of the mold with a mixed liquid formed by mixing the raw materials of the modified polyvinyl alcohol layer and heating to cure; then coating the hollow part of the mold with a mixed liquid formed by mixing the raw materials of the radiation source layer and heating to evaporate the organic solvent to form a radiation source layer; and finally removing the mold, further coating the mixed liquid formed by mixing the raw materials of the modified polyvinyl alcohol layer on the radiation source layer and heating to cure.
10. Use of the radioactive source film as claimed in any one of claims 1 to 4 as a standard source and / or a signal detection source and / or a nuclear battery power generation energy source.